Possibility of using rebus sic stantibus clause for the protection of parties of contractual relations affected by the effects of SARS-COV-2 - Barylska, Michalina; Deka, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
This article deals with the problem of application of rebus sic stantibus clause, set forth in Art. 357(1) of the Civil Code, in conjunction with announcing by the Minister of Health a state of epidemiological emergency in the territory of the Republic of Poland, and, subsequently, the state of SARS-CoV-2 epidemic. This article aims to determine whether it is permissible to apply the foregoing clause in order to mitigate the effects of the pandemic that may affect a party to contractual relationships and also in relation to which contracts the foregoing clause shall be applicable. The authors analyse, under what circumstances it shall be possible to apply to a court the amount of performance or with a motion to terminate a contract. Attention was drawn to the necessity to have a narrow interpretation of the norm set forth in Art. 357(1) of the Civil Code. An opinion has been presented in this article that the effectiveness of rebus sic stantibus clause may be affected by an admissibility to formulate a claim in pursuance of Art. 357(1) of the Civil Code. of law with a motion to determine a manner of performing anobligation, with a motion to change the amount of performance or with a motion to terminate a contract. Attention was drawn to the necessity to have a narrow interpretation of the norm set forth in Art. 357(1) of the Civil Code. An opinion has been presented in this article that the effectiveness of rebus sic stantibus clause may be affected by an admissibility to formulate a claim in pursuance of Art. 357(1) of the Civil Code.